RELATIONSHIP BETWEEN LOCATION FACTORS AND RESIDENTIAL CHOICE IN SUNGAI RAYA DALAM VILLAGE - Carissa, Carissa; Sulistyarini, Sulistyarini; Harjanti, Diah Trismi (GEOREFERENCE, 2024)
Sungai Raya Dalam Village is part of an area located on the outskirts of Pontianak City. The rapid growth of Pontianak City has had an impact on Sungai Raya Dalam Village, one of which is the need for housing. The increasingly expensive need for housing in urban areas makes people choose to live in suburban areas. The research aims to describe the relationship between location factors and the choice of residence in Sungai Raya Dalam Village. This form of research is descriptive quantitative research. This study had a population of 6,269 heads of families and the sample was calculated using the Slovin formula so that a sample of 98 respondents was obtained. The methods for collecting data were used as follows: primary survey techniques, secondary survey techniques, documentation study techniques, and literature study techniques. The tools and materials used to collect data in this research were: a  laptop, SPSS version 27, and questionnaires. The relationship between location factors and choosing a place to live in Sungai Raya Dalam Village is -0.253, according to the results of research conducted using the product moment correlation technique. The results of statistical calculations show the calculated r = -0.253 compared to the r table of 0.195, with a significance level of 5%.